Synthesis and characterization of strontium-doped hydroxyapatite powder via sol-gel method - Mardziah, C.M.; Sopyan, I.; Abd Shukor, Mohd Hamdi; Ramesh, S. (Malaysian Medical Association, 2008)
Improvement of the mechanical properties of hydroxyapatite (HA) can be achieved by the incorporation of metal. In addition, incorporation of strontium ion into HA crystal structures has been proved effective to enhance biochemical properties of bone implant. In this research, strontium-doped HA powder was developed via a sol-gel method to produce extraordinarily fine strontium-doped HA (Sr-doped HA) powder. XRD measurement had shown that the powder contained hydroxyapatite phase only for all doping concentration except for 2, showing that Sr atoms have suppressed the appearance of beta-TCP as the secondary phase. Morphological evaluation by FESEM measurement shows that the particles of the Sr-doped HA agglomerates are globular in shape with an average size of 1-2 microm in diameter while the primary particles have a diameter of 30-150 nm in average.